Paleohistology and the study of human remains: past, present and future approaches - Assis, Sandra (2016)
The invention of the microscope revolutionized the course of human knowledge. This instrument changed the face of science and of previous beliefs, expanded the horizons of knowledge, and challenged philosophical and scientific thought, especially in the field of natural sciences and medicine. In the domain of bioarchaeology, the introduction of histological techniques was important; not only to identify body tissues and to diagnose diseases in mummified remains, but also to understand bone and teeth microstructure, and associated patterns of response to environmental constraints. In this paper a critical review of the major contributions of histology to the growing body of knowledge in paleopathology and bioarchaeology will be presented, focusing on the current multiple applications of microscopy, its limitations, and its future challenges.